Performance analysis of flow channel collector for photovoltaic thermal system - Umam, Mukhamad Faeshol; Hasanuzzaman, Md.; Selvaraj, Jeyraj (International Journal of Renewable Energy Development, 2026)
Solar energy has seen the most significant development in the past decade. Electricity and hot water production are the two most common uses of solar energy. A photovoltaic (PV) system is a popular method for generating electricity from solar energy. However, PV systems are known for their low efficiency, which reduces further as the PV cell temperature rises. The photovoltaic-thermal (PVT) system combines a PV system with a thermal collector to provide dual benefits, namely power generation and hot water production. However, PVT system research often employs a constant flow (CF) strategy in which water is continually cycled throughout the experiment, making it inapplicable. In comparison, the constant collection temperature (CCT) scheme is a more feasible approach, but its impact on PVT system performance has received less attention. This study compares a flow channel PVT system using both CF and CCT strategies. The results show that the CF scheme achieved a higher maximum thermal efficiency of 35.05%, while the CCT scheme reached 17.89%. The CCT method can also maintain the optimum water temperature despite changing radiation circumstances. The PVT system outperforms traditional PV panels regarding electricity efficiency, with a maximum improvement of 0.89% and 0.96% utilizing the CF and CCT schemes, respectively. These results show that PVT systems with CCT schemes that use less energy for pumping outperform PV panels in terms of power production and electricity efficiency.